2010
DOI: 10.1007/s11999-009-0892-9
|View full text |Cite
|
Sign up to set email alerts
|

The Chitranjan Ranawat Award: The Nonoperated Knee Predicts Function 3 Years after Unilateral Total Knee Arthroplasty

Abstract: The long-term functional abilities of patients after a unilateral total knee arthroplasty (TKA) are influenced by the status of the nonoperated knee at the time of the TKA. We hypothesized that in the 3 years after TKA, the nonoperated limb would become more painful, and the quadriceps muscles would weaken; pain and strength would influence performance on functional testing by 3 years after TKA. Healthy control subjects were tested over the same time interval; we hypothesized the controls would also decline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 29 publications
3
72
0
Order By: Relevance
“…Among studies of musculoskeletal comorbidities, those related to pain in joints other than the operatively treated knee, in particular, have described interesting results. For instance, preoperative pain in the nonoperatively treated knee was associated with poorer knee performance at three years after total knee replacement 4 . Low back pain was shown to predict poorer physical function after primary total knee replacement 5 and was associated with poorer function scores at twelve months and twenty-four months after revision total knee replacement 6 .…”
Section: Level Of Evidence: Prognostic Level II See Instructions Formentioning
confidence: 99%
“…Among studies of musculoskeletal comorbidities, those related to pain in joints other than the operatively treated knee, in particular, have described interesting results. For instance, preoperative pain in the nonoperatively treated knee was associated with poorer knee performance at three years after total knee replacement 4 . Low back pain was shown to predict poorer physical function after primary total knee replacement 5 and was associated with poorer function scores at twelve months and twenty-four months after revision total knee replacement 6 .…”
Section: Level Of Evidence: Prognostic Level II See Instructions Formentioning
confidence: 99%
“…predictors of post-arthroplasty function have not examined the impact of contralateral knee symptoms, although a few recent studies have demonstrated that post-arthroplasty factors in the contralateral knee, such as strength 7 and pain 8 , are associated with post-arthroplasty function. As some of the effects of postarthroplasty contralateral knee symptoms on function may be due to contralateral impairments that developed as a consequence of surgery, increasing the demand on the contralateral knee, it is important to study both the pre-arthroplasty status and the post-arthroplasty status of the contralateral knee.…”
mentioning
confidence: 99%
“…7 This loss of strength is exemplified by a reduction in the contribution of the knee extensor moment during loading response in the nonoperated limb by 1 year after TKA. 32 As a result, bilateral strength deficits may underlie the gait abnormalities in patients after TKA compared to age-matched healthy individuals.…”
mentioning
confidence: 99%